Comparative Study of Liquid Biodiesel From Sterculia foetida (Bottle Tree) Using CuO-CeO2 and Fe2O3 Nano Catalysts - Akhtar, Maryam Tanveer; Ahmad, Mushtaq; Shaheen, Anjuman; Zafar, Muhammad; Ullah, Riaz; Asma, Maliha; Sultana, Shazia; Munir, Mamoona; Rashid, Neelam; Malik, Khafsa; Saeed, Muhammad; Waseem, Amir (Frontiers in Energy Research, 2019)
This study examined the potential of Nanocatalyst CaO.CeO2 and Fe2O3 for efficient conversion of Sterculia foetida seed Oil into biodiesel. Sterculia foetida contains oil content 40% and low free fatty acid value (0.18mg KOH/g). The synthesized Nanocatalyst were characterized using X-Ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR) and Scanning Electron Microscopy (SEM) techniques. The maximum conversion was achieved (92% yield) using CuO.CeO2 at 0.25% catalyst loading. The optimized reaction was carried out by experimental variables included molar ratio (1:3), temperature (700C), reaction time (3hrs) and stirring rate (600rpm) using reflux transesterification method. The XRD results showed the size of crystals with order 54.4nm for CuO.CeO2 and 31.3nm for Fe2O3. The SEM images of CuO.CeO2 showed spherical structure having particle size of 32.3nm. SEM images of Fe2O3 showed the size ranges from 46.27nm to 28.76nmhaving regular morphology including spherical shape. The FT-IR analysis of these Nanocatalyst also reinforced the results of this study. Gas Chromatography Mass Spectroscopy (GC-MS) and Fourier Transform Infrared Spectroscopy (FT-IR) confirmed the efficient conversion of Sterculia foetida seed oil into biodiesel using prepared nano-catalysts. The prepared nano-catalysts are cheaper, readily available and can be used for industrial scale biofuel production assembly it economically feasible and more cost effective.